Implementasi Keterwakilan Perempuan Anggota Dewan Perwakilan Rakyat Daerah di Kabupaten Sukoharjo - Afwah Rafi Miftah Supriyadi; Asmorojati, Anom Wahyu (Media of Law and Sharia, 2024)
The lack of support hampers the performance of female legislators. This is one of the obstacles in achieving 30 percent female representation in the legislature. In its implementation, there has been a law that regulates political parties and elections that provides opportunities for women to enter politics and participate in parliament. This study aims to find out the comparison of the implementation of women's representation in members of the Regional People's Representative Council (DPRD) in Sukoharjo Regency in the 2014-2019 period and the 2019-2024 period and the factors that cause instability in women's representation in the DPRD. The author uses empirical juridical research methods and uses primary and secondary data sources. The authors collected data through literature studies and field studies. The data collection method was carried out by observation, interviews, and questionnaires. The data analysis method is used to analyze data obtained from literature studies and interview results, which are then analyzed descriptively and qualitatively to obtain the facts and realities revealed in the research. The results of the study show that first, the representation of women in the membership of the DPRD in Sukoharjo Regency in the 2014-2019 period and the 2019-2024 period has not been able to meet 30 percent of women's representation. When presented in the 2014-2019 period, women's representation was 15.56%, while in the 2019-2024 period, women's representation was 22.22%. Although it has increased, the increase has not been able to meet the 30% representation of women in the legislature. The government continues to strive to fulfill the 30% percentage of female representation. Furthermore, the factors that cause instability in women's representation include political and cultural barriers, obstacles from within women, social and economic obstacles to candidacy